The Effect of Differentiated Science Inquiry Learning Model Based on Teaching at the Right Level on Students’ Critical Thinking and Science Process Skills - Ramlawati, Ramlawati; Sari, Nur Indah; Kusumawati, R.; Yesin, M.; Ilmi, N.; Arsyad, Arie Arma (Universitas Negeri Semarang, 2025)
Student cognitive diversity can be a barrier to enhancing critical thinking and science process skills. The TaRL-based DSI model addresses this by facilitating learning for students at different cognitive levels. This research aims to determine the effect of the Differentiated Science Inquiry (DSI) model based on the Teaching at the Right Level (TaRL) approach on eighth-grade junior high school students’ critical thinking and science process skills in the context of vibration and wave concepts. A non-equivalent control group design was used to address varied learning needs, with 55 students purposively selected for experimental and control groups. Data were collected using essay-based critical thinking tests and multiple-choice science process skills assessments. The DSI model applied four inquiry levels: Demonstrated Inquiry, Structured Inquiry, Guided Inquiry, and Self-Directed Inquiry based on students’ initial abilities. Data were analyzed using descriptive and inferential methods. The average critical thinking skills in the experimental group after treatment were 13.04, and in the control group were 10.1. The average science process skills in the experimental group were 19.77, and in the control group were 18. The research results confirm that the TaRL-based DSI model significantly enhances students’ critical thinking and science process skills at a significance level of α = 0.05. This research is expected to help educators implement the DSI model to accommodate diverse learning needs and enhance crucial skills in science education.